Review of Microgrids and Associated Protective Systems - , Maruf A. Aminu (Archives of Current Research International, 2019)
In this century, the human appetite for electrical energy is the highest in history. This high demand for electricity results in increased need for power generation. The current power network is put under pressure to ensure high-quality generation, transmission and distribution of power. The network, in most countries, is aging – requiring higher resources in order to satisfy present-day challenges, in addition to the need to minimize power losses and optimize power production. These challenges have necessitated innovative power production techniques, such as the microgrid. The operation of microgrid comes with emerging challenges. This paper articulates and reviews some of the most noticeable challenges of utility and microgrid operations. The paper also presents some of the recent proposals for microgrid protection, as well as the limitations associated with these proposals.